Private guns, public health - Hemenway, David, 1945- (University of Michigan Press, 2017)
"On an average day in the United States, guns are used to kill over ninety people and wound about three hundred more; yet such facts are accepted as a natural consequence of supposedly high American rates of violence. Private Guns, Public Health reveals the advantages of treating gun violence as a consumer safety and public health problem--an approach that emphasizes prevention over punishment and that has successfully reduced the rates of injury and death from infectious disease, car accidents, and tobacco consumption. Hemenway fair-mindedly and authoritatively outlines a policy course that would significantly reduce gun-related injury and death, pointing us toward a solution"--Publisher's description